Student Migration to the EU from Non-EU Countries - In, Seolah; Shymanska, Kateryna; Abdallah, Kareem Issam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis provides an analysis of non-EU student migration into the European Union (EU), describing migration drivers, outcomes, and policies in all 27 EU member states. Using OLS regression analysis, it concludes that population size and unemployment are the main drivers. It further questions the economic assumptions behind migration. It also finds that 30 percent of international students, compared with only 19 percent of domestic students, have enrolled in science, technology, engineering, and mathematics (STEM) subjects. They are therefore recognized as a planned resource for addressing skill and labor shortages in science, technology, engineering and mathematics in Europe. Germany, Ireland and the Netherlands are case studies of the influence that policy context has on the retention of graduates from EU countries, with exit rates ranging from below 10 percent to above 60 percent. The cost of education abroad has a meaningful economic impact on host countries, in the form of tuition, living and other expenses, and graduates are often earning equal or better pay. The study's results suggest that access to labour markets, rather than wage equity concerns, explain destination choice. Further, there is a need for good post-study work policies and integration schemes to convert educational mobility into medium- to long-term skills/career development and remedying STEM labour shortages in the contemporary European context.
Vedoucí práce: Kateryna Shymanska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses